Some adaptations of myrmeleontid (Neuroptera) and rhagionid (Diptera) larvae to life in hot dry sand - Youthed, Gayle Jean (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1974)
From Introduction: Larvae of the families Myrmeleontidae, Neuroptera, (ant-lions) and Rhagionidae, Diptera, (worm-lions) all live in hot dry sand. Many of the ant-lion larvae and all the worm-lion larvae, construct small conical pits in the sand which are used for the capture of prey (Haub, 1942; Youthed and Horan, 1969a). Those ant-lion larvae which do not construct pits lie in wait for their prey just below the surface of the sand.
Keywords: Ant lions; Rhagionidae